Compersion of primary unsulfated bile acid levels during the different stages of childhood period with adult values in spot urine - Ömer NASIROĞLU,; Tülay AYDIN,; Can FIÇICIOĞLU,; Halit ÇAM,; Şerare MIKLA,; Gülsev KAVUNOĞLU,; Sebati ÖZDEMİR,; Ahmet AYDIN, (Turkish Journal of Gastroenterology, 2019)
-